Pengaruh Pemberian MOL Rebusan Kedelai untuk Meningkatkan Pertumbuhan dan Hasil pada Tiga Varietas Sawi - Roni, Mohammad; Fitri Mei Arini , Silvia (JURNAL AGROPLANT, 2023)
This study aims to determine the mole dosage of soybean stew and the 3 best varieties for the growth and production of mustard greens. This research was conducted in Krajan Hamlet, Sukorambi Village, Sukorambi District, Jember, East Java. from November 2022 to January 2023. The study was conducted using a factorial pattern with a randomized block design (RBD) consisting of 2 factors and 3 replications. The first factor is the fertilization dose treatment (D), which consists of 5 levels, namely (control) D0= 0 m1/1, D1= 25 m1/1, D2= 50 m1/1, D3= 75 m1/1, D4= 100 m1/1 1, and the second factor was 3 different mustard varieties (V) which consisted of 3 levels, namely V1= caisim green mustard, V2= pakcoy mustard, V3= chicory. Parameters observed were number of leaves, plant height, leaf width, leaf length, fresh weight, and root length. The collected data were analyzed by means of variance (Anova), if significantly different it was continued with Duncan's test at the 5% level using Microsoft Excel. The results showed that the mole dose treatment of soybean stew showed no significant difference and the treatment of 3 different varieties showed significantly different results on plant height and fresh weight parameters.